Excitatory amino acid antagonists and pentylenetetrazol-induced seizures during ontogenesis. IV. Effects of CGP 39551 - Velísek, L; Vachová, D; Mares, P (Pharmacology, biochemistry, and behavior, 1997)
We determined anticonvulsant effects of CGP 39551 [(E)-2-amino-4-methyl-5-phosphono-3-pentenoic acid 1-ethylester] against pentylenetetrazol-induced seizures in developing, 7-90 day old, rats. The rats received CGP 39551 in doses of 10, 20 or 40 mg/kg IP 30 min prior to the pentylenetetrazol administration (100 mg/kg s.c.). In addition, the 20 mg/kg dose of CGP 39551 was injected 120 min prior to pentylenetetrazol. In adult rats, all doses of CGP 39551 blocked generalized tonic-clonic pentylenetetrazol-induced seizures. In younger rats, higher doses of CGP 39551 and/or a longer delay between the CGP 39551 pretreatment and pentylenetetrazol administration was necessary for similar anticonvulsant effects against tonic-clonic seizures. In contrast, there was no effect of CGP on pentylenetetrazol-induced clonic seizures. The results indicate that CGP 39551 has anticonvulsant features similar to other competitive NMDA receptor antagonists. High doses of CGP 39551 and long pretreatment latency which are necessary in young rats for anticonvulsant effects may reflect the overexpression of NMDA transmission during the second and third postnatal week of the rat. Alternatively in adult rats, we can speculate an anticonvulsant role of a CGP 39551 metabolite or maturation of brain uptake mechanism for CGP 39551.
Keywords: Male; konvulziva; Rats, Wistar; preklinické hodnocení léčiv; 2-amino-5-fosfonovalerát; mužské pohlaví; potkani Wistar; Anticonvulsants; krysa rodu Rattus; Convulsants; Animals; Epilepsy, Tonic-Clonic; epilepsie tonicko-klonická; 2-Amino-5-phosphonovalerate; Pentylenetetrazole; Drug Evaluation, Preclinical; zvířata; Rats; antikonvulziva; antagonisté excitačních aminokyselin; pentylentetrazol; Excitatory Amino Acid Antagonists